Hubungan Pemakaian Jenis Sikat Gigi Dengan Status Gingiva Pada Siswa Pengguna Alat Orthodontik Cekat di Sekolah Menengah Atas - Zul Afni; Dwi Suyatmi; Etty Yuniarly (Journal of Oral Health Care, 2018)
Dental and oral diseases are still suffered by 25,9 % of Indonesia's population. Based on that percentage 31,1 % are receiving treatment and treatment from dental medical personnel, while 68,9 % are not treated. The use of orthodontic devices has spread among teenagers, especially high school children aged 14-17 with the aim of following trends and lifestyles without thinking about the impact. According to World Health Organization, schools and adolescents are important target groups for an oral health examination. To know the correlation of use of toothbrush type with gingival status on fixed orthodontic user students. This research type is analytic observation with a cross-sectional design. This study was conducted in October-November 2017. The study population of this study is the students of class X who wear the fixed orthodontic appliance. Data analysis used chi-square. Respondents of fixed orthodontic appliance users orthodontic toothbrush are 60,5 %. Respondents of fixed orthodontic appliance users had a healthy gingival status is 57,9 %. The result of statistical analysis obtained significant value = 0,029<0,05. The type of toothbrush used has a correlation with the status of the gingiva on the students of a fixed orthodontic appliance.